ANALISIS PERSEPSI STAKEHOLDER TERHADAP RENDAHNYA LAYANAN ADMINISTRASI DI SEKOLAH SMA DARUL ULUM BANYUPUTIH - Luluk Mashluchah; Samsuri (Nusantara Journal of Islamic Studies, 2023)
In this study, the researcher used qualitative research. The type of research in this study uses a qualitative approach, namely describing and analyzing the problems found. Qualitative research is based on primary and secondary data. Primary data is obtained through interviews, while secondary data is obtained through documentation photos from informants related to the study. The purpose of this study is to analyze the low level of school administration services at SMA Darul Ulum Banyuputih. In order to improve administrative services to be better and understand the factors that contribute to administrative services and analyze the impact of low administrative services to formulate recommendations and strategies for improving administrative services. The results of this study indicate that the low factors that make administrative services low are human resources factors, lack of training in the use of new technology and service facility factors. The impact faced in administrative services at SMA Darul Ulum Banyuputih is the lack of focus on work due to the absence of a clear organizational structure in the field of service administration. In terms of facilities and infrastructure, improvements must be made so that the administrative service process runs well. Increase quality and provide training to employees to maximize performance.